2010
DOI: 10.2190/om.60.2.b
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spirituality, Religiosity, and Denial in Individuals Working in Funeral Service to Predict Death Anxiety

Abstract: The aim of the present study was to examine predictors of death anxiety in U.S. funeral directors/embalmers who were part of a larger study (n = 234). Backward stepwise multiple regression was conducted to determine whether or not spirituality, intrinsic religiosity, extrinsic religiosity, and denial predicted levels of death anxiety. Results indicated that spirituality along with age of the participants accounted for 19% of the variance of death anxiety, R2 = .190, R2(adj) = .180, F(2, 168) = 19.64, p < .001.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
1
3
0
1
Order By: Relevance
“…These findings contribute to our understanding of this understudied population, who appear to possess relatively high capacities for openly confronting and processing threatening or stressful stimuli. These findings extend past work focusing on the predictors of death anxiety within funeral/ cemetery workers (e.g., Harrawood, 2010), by considering the predictors of more positive forms of psychological functioning within this population.…”
Section: Discussionsupporting
confidence: 83%
“…These findings contribute to our understanding of this understudied population, who appear to possess relatively high capacities for openly confronting and processing threatening or stressful stimuli. These findings extend past work focusing on the predictors of death anxiety within funeral/ cemetery workers (e.g., Harrawood, 2010), by considering the predictors of more positive forms of psychological functioning within this population.…”
Section: Discussionsupporting
confidence: 83%
“…Prior adult evidence suggests that funeral professional often encounter anxiety in delivering unique funerals or those that involve sudden loss. 7,8 Although improved partnerships with pastoral care to assist with bereavement has been suggested for funeral professionals, 6 training in emotional intelligence might also be an important option for these professionals. 15 Emotional intelligence training is a set of practical skills that help individuals become fluent in understanding their own and others' emotions and support their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The bereavement experiences associated with the loss of a child deeply impact funeral home staff, and can create either a deeply negative or positive experience for families. 3,4 Although several studies have focused on funeral professionals and adult services, [5][6][7][8] an emerging literature suggests that funeral professionals might have a significant role in providing services to families upon the death of a child. Michaelson and Lund examined the role and found that the characteristics of funeral professionals include service, commitment, genuine care, compassion, ability to communicate and listen, confidentiality, conscientiousness, honesty, physical strength, supporting families, and restorative art.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiritualitas merupakan salah satu faktor yang mempengaruhi kesiapan sesorang menghadapi kematian (Khanna & Greyson, 2014). Lansia yang mampu menerima kondisi kenyataan hidup tanpa penyesalan dan perasaan putus asa akan lebih siap mengadapi kematian tanpa muncul rasa kecemasan (Harrawood, 2010). Spiritualitas dibutuhkan lansia dalam menghadapi hari tua.…”
Section: Pendahuluanunclassified